Developing speaking skills in large classes - Alpaca Olortegui, Adela Hermes (2021)
The main reason for me is let you known the great importance of communicating fluently in a second language. Nowadays traveler student has the necessity to master a new language because we are in globalize world. Therefore, graduates from school need to be prepared in all four skills as a listening, speaking, writing, grammar and sub-abilities like phonetic and phonology and others and words are going to come out one after another in abundance. Students will find facts and ideas as a result an excellent speech. Learning foreign languages allows us to be ahead in the future and starting from childhood knowing several ones to be prepared for tomorrow. Opinions of different authors about “Developing speaking skills in large classes” has allowed me to reinforce the elaboration of how to reach students and turn them into good speakers It is a little difficult to educate to many students but with a good motivation, affection, character, knowledge and example of the teacher it can be achieved at 98 percent of a real goal. I must say the didactics is an essential element for educate considering first the method, approach, technique, strategies and develop a good methodology to teach. Finally, a professor has to be clear the objective of the goal to dealt academic and formation personal to form with a solid base to the students of today, great professionals of tomorrow.